Recognition of tachyzoite and bradyzoite antigens of Toxoplasma gondii by infected hosts. - Makioka, A (1991)
Western immunoblots of tachyzoite and bradyzoite antigens of Toxoplasma gondii were probed with antisera from rabbits and mice at intervals between 2 and 8 weeks after infection and with human antisera with various titers of antibody. With rabbit and mouse antisera, two groups of antigens with molecular masses of 54 to 63 kDa (designated 58.5-kDa antigens) and 26 to 29 kDa (designated 27.5-kDa antigens) were demonstrated commonly for both stages, while those antisera reacted strongly with tachyzoite (but not bradyzoite) antigens with molecular masses of 29 to 54 kDa. Tachyzoite antigens of 21.5, 26.5, 31, 38, 40, 49, and 58 kDa reacted with antisera 2 to 4 weeks after infection, while bradyzoite antigens of 27, 51, 220, and 290 kDa reacted with antisera obtained 4 or more weeks after infection. The 58.5-kDa antigens of both stages reacted primarily with human antisera that had low titers of anti-T. gondii antibodies. Human (as well as rabbit and mouse) sera with high antibody titers reacted with the 27.5-kDa antigens as well as the 58.5-kDa antigens, but the reactivity of the 27.5- to 58.5-kDa antigens of tachyzoites was greater than that of bradyzoites.